Length–weight relations and condition factors of several endemic and native fish species from Anatolian freshwater - Onay Hatice; Kurtul Irmak; Kaya Cüneyt; Turan Davut; Bayçelebi Esra (Oceanological and Hydrobiological Studies)
This study analyzed the length–weight relations and condition factors of 13 species belonging to three highly endemic genera: Oxynoemacheilus (6), Seminemacheilus (2) and Cobitis (5). Fish were sampled in several streams and lakes using a backpack electroshocker. Analyses were based on a total number of individuals, which was n = 304. A linear regression model was applied to determine the relationship between fish length and weight. The coefficient of determination (R2) ranged from 0.950 to 0.980 for all populations (p < 0.05). Allometric coefficient ‘b’ values ranged from 2.498 to 3.201 for Oxynoemacheilus, from 2.970 to 2.127 for Seminemacheilus, and from 2.111 to 3.076 for Cobitis populations. Fulton’s condition factor for Oxynoemacheilus, Seminemacheilus and Cobitis ranged from 0.391 to 3.080. This study addresses gaps in LWR and CF information for a number of ecologically important freshwater fish species. It is expected that the results of this research provide baseline data for further fisheries management studies and may support conservation studies of related species.